Niche partitioning between species of the Leptodactylidae family: a brief account of siblings (Research, Society and Development, 2022)
Studies on the partition of resources between phylogenetically related amphibian species are scarce for the Caatinga domain, with most studies developed for the Atlantic Forest region. Therefore, the objective was to evaluate the spatial and temporal distribution pattern of 9 species of the Leptodactylidae family in the Caatinga region of the State of Pernambuco. Observations were carried out using the Time Limited Visual Search (PVLT) method for 18 months in the vicinity of the Cachoeira de Maria Mendes rural property in the municipality of Tabira. There were 594 sightings of individuals belonging to 9 species belonging to the Leptodactylidae family. Analyzes were carried out to evidence the overlap of habitat use and to relate richness versus abiotic variables. The results suggested maximum overlap of habitat use, however, the smallest overlap was evidenced for the species Leptodactylus troglodytes versus Leptodactylus fuscus that integrate the fuscus group of the Leptodactylidae family. In addition, all species sampled showed generalist behavior regarding habitat use, with a higher occurrence in anthropic environments.